Obesity as A Risk Factor For Severe COVID-19 Disease - Sajjad, Muhammad Mohsin; Nasir, Adnan; Yousaf, Sidra; Abdul Rahim, Muhammad Waseel (Pakistan Armed Forces Medical Journal, 2022)
Objective: To explore the risk factors for severe COVID-19 disease.Study Design: Case series.Place and Duration of Study: Cavan General Hospital, Ireland, from Mar to May, 2020.Methodology: All the admitted patients with laboratory confirmed COVID-19 infection were included in the study. Patients on non-invasive ventilation, in the Intensive Care Unit and on mechanical ventilation within the first 10 days of hospital admission were included in the study. The demographics, clinical details, radiological and laboratory findings were collected from the medical records.Results: A total of 17 patients who required non-invasive ventilation/continuous positive airway pressure were included in the study. All patients were obese/overweight. Five patients required Intensive Care Unit admission and were subsequently intubated for mechanical ventilation. One patient died in ICU.Conclusions: Obesity is a significant risk factor for severe COVID-19 disease, recognition of high-risk population could help clinicians identify patients with severe disease at an early stage.